Incoherences and Incompatibilities: Just Peace and Just War in Contemporary German Protestantism - Feiler, Therese (Studies in Christian ethics, 2024)
This article revisits some of the main tenets and problems of the Just Peace concept as developed in the German Protestant Church, showing how it is beset by incoherences, ironical returns of expanded violence, as well as the problem of abstraction: once the Just Peace concept is applied to concrete problems, it runs dry. The article then examines some recent contributions made under the wider umbrella of ‘peace ethics’, showing that attempts to combine the Just Peace and bellum iustum are bound to fail. It then retraces the present shift to Just War thinking that reorders the basic terms, whilst also retaining some of the tenets of the Just Peace approach. Some refinements of these developments are indicated.